Plain carbon steel with ultrathin iron-based coating and manufacturing method of plain carbon steel

By using HDED technology to prepare ultra-thin iron-based coatings on the surface of ordinary carbon steel, the problem of insufficient wear and corrosion performance of steel plates in the prior art is solved, and the wear resistance and corrosion resistance of steel plates are significantly improved.

CN119433528APending Publication Date: 2025-02-14BAOSHAN IRON & STEEL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310939949.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

High-speed direct energy deposition (HDED) technology has not been used in the prior art to improve the wear and corrosion performance of steel plates.

Method used

Ultra-thin iron-based plating is prepared by using high-speed direct energy deposition process (HDED) on the surface of ordinary carbon steel. The plating is made of layered sheet structures made of iron-based alloy powder stacked, combining electrochemical plating methods and thermal isostatic pressure treatment.

Benefits of technology

The wear resistance and corrosion resistance of the steel plate are significantly improved, greatly improving the life of the material during service. At the same time, the bonding of the iron-based plating layer and ordinary carbon steel substrate is better.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004364807510000051
    Figure BDA0004364807510000051
  • Figure BDA0004364807510000052
    Figure BDA0004364807510000052
  • Figure BDA0004364807510000061
    Figure BDA0004364807510000061
Patent Text Reader

Abstract

The invention discloses plain carbon steel with an ultrathin iron-based coating, which comprises a plain carbon steel base material and is characterized in that the surface of the plain carbon steel base material is provided with the iron-based coating, and the iron-based coating is of a lamellar structure formed by stacking iron-based alloy powder. Correspondingly, the invention also provides a manufacturing method of the plain carbon steel with the ultrathin iron-based coating, which comprises the following steps: depositing the iron-based alloy powder on the surface of the plain carbon steel substrate by adopting a high-speed direct energy deposition process to form the iron-based coating, and controlling the deposition speed to be 20-60m / min; and carrying out hot isostatic pressing treatment on the iron-based coating. According to the plain carbon steel with the ultrathin iron-based plating layer, the binding property of the iron-based plating layer and a plain carbon steel base material is good, and in addition, the plain carbon steel has excellent wear resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel plate and a manufacturing method thereof, and in particular to a steel plate with a coating and a manufacturing method thereof. Background Art

[0002] Additive Manufacturing (AM) is an evolving technology that has been widely used in many metal applications. In recent years, a great deal of work has been done in science and engineering to significantly advance the commercialization of metal AM technologies. The unique advantage of AM technologies for manufacturing metal parts is their ability to deliver customized or complex parts in a very short time compared to traditional manufacturing techniques.

[0003] High-speed direct energy deposition (DED) and even ultra-high-speed direct energy deposition (EHDED) are the latest AM technologies that can solve efficiency bottlenecks and promote grain refinement. HDED is considered to be the best alternative to HCP and thermal spraying.

[0004] For example, the use of HDED to prepare Ti-Cu-NiCoCrAlTaY coating on the surface of TC4 alloy can improve its anti-oxidation and anti-combustion properties. This is because a dense composite oxide film is formed on the surface of the coating, which has good oxidation properties.

[0005] For another example, HDED coating is conducive to the completion of pre-oxidation and the formation of continuous oxide film, which indicates that HDED coating has better high temperature resistance than thermal spray coating.

[0006] However, in the prior art, there is no technical solution for preparing coatings using HDED to improve wear and corrosion performance. Summary of the invention

[0007] One of the purposes of the present invention is to provide a plain carbon steel with an ultra-thin iron-based coating. The coating is prepared on the surface of plain carbon steel as a working electrode based on an electrochemical plating method, so that the surface roughness of the plain carbon steel is increased and the specific surface area is also increased. The iron-based coating prepared by multi-layer electrodeposition has good bonding with the plain carbon steel substrate. At the same time, the lamellar structure of the iron-based coating greatly improves the wear resistance and corrosion resistance of the coating itself, thereby greatly improving the service life of the material during service.

[0008] In order to achieve the above-mentioned purpose, the present invention provides a plain carbon steel with an ultra-thin iron-based coating, which includes a plain carbon steel substrate, the surface of the plain carbon steel substrate has an iron-based coating, and the iron-based coating is a lamellar structure formed by stacking iron-based alloy powders.

[0009] Furthermore, in the plain carbon steel with an ultra-thin iron-based coating described in the present invention, the iron-based alloy powder contains Cr and C elements.

[0010] Furthermore, in the plain carbon steel with an ultra-thin iron-based coating described in the present invention, the iron-based alloy powder may contain 0.2-0.6% Cr and 0.2-0.4% C.

[0011] Furthermore, in the plain carbon steel with the ultra-thin iron-based coating described in the present invention, the iron-based coating is stacked by a high-speed direct energy deposition (HDED) process.

[0012] The high-speed direct energy deposition described in the present invention may refer to laser directed energy deposition (DED) technology, in which a laser generates a molten pool in a deposition area and moves at high speed, and the material is directly fed into a high-temperature melting zone in powder or filament form, and deposited layer by layer after melting.

[0013] Furthermore, in the plain carbon steel with the ultra-thin iron-based coating described in the present invention, the single-side thickness of the coating is 60-150 microns.

[0014] Furthermore, in the plain carbon steel with ultra-thin iron-based coating of the present invention, the hardness of the iron-based coating is 670-1220 HV, and the corrosion current density is 0.9 μA / cm 2 the following.

[0015] Another object of the present invention is to provide a method for manufacturing plain carbon steel with an ultra-thin iron-based coating. The method coats the surface of plain carbon steel through a high-speed direct energy deposition process (HDED), thereby increasing the surface roughness of the plain carbon steel and the specific surface area, so that the iron-based coating has better bonding with the plain carbon steel substrate. At the same time, the lamellar stacked iron-based coating greatly improves the wear resistance and corrosion resistance of the coating itself, thereby greatly improving the service life of the material during service.

[0016] In order to achieve the above object, the present invention also provides a method for manufacturing plain carbon steel with an ultra-thin iron-based coating, which comprises the steps of:

[0017] A high-speed direct energy deposition process is used to deposit iron-based alloy powder on the surface of a plain carbon steel substrate to form an iron-based coating, wherein the deposition speed is controlled to be 20-60 m / min;

[0018] The iron-based coating is subjected to hot isostatic pressing.

[0019] In the manufacturing method described in the present invention, the deposition speed is controlled to be 20-60m / min because the speed of the deposition rate can directly affect the quality of the surface coating. If the deposition rate is too fast, the coating will not have enough time to stably combine with the metal substrate, which will cause the coating to fall off easily during subsequent use; if the deposition rate is too slow, the coating structure will be stratified and uneven, which will affect the coating efficiency and increase the coating cost.

[0020] Furthermore, in the manufacturing method described in the present invention, the parameters of the high-speed direct energy deposition process meet the following requirements: the power stability of the fiber laser is 1-3%, and the central wavelength is 900-1080 nm.

[0021] Furthermore, in the manufacturing method described in the present invention, the parameters of the high-speed direct energy deposition process meet the following requirements: the feeding speed of the powder feeder is 60-150 g / min.

[0022] In the present invention, the iron-based alloy powder can be introduced from the outside into the powder feeder or powder storage inside the machine, so as to complete the feeding at a relatively fast speed. When a certain amount of powder is in the powder storage, the spraying preparation of the coating is started, and the powder in the powder storage is sprayed onto the surface of the metal substrate.

[0023] Furthermore, in the manufacturing method described in the present invention, the parameters of the hot isostatic pressing treatment meet at least one of the following items: laser power is 2200-3000W, overlap rate is 50-70%, powder feeding rate is 10-15g / min, laser spot diameter is 0.8-1.2mm, and defocus amount is 5-10mm.

[0024] Furthermore, in the manufacturing method of the present invention, the diameter of the iron-based alloy powder is in the range of 25-53 μm.

[0025] The plain carbon steel with ultra-thin iron-based coating of the present invention has the following beneficial effects:

[0026] The iron-based coating in the ordinary carbon steel with an ultra-thin iron-based coating of the present invention has good bonding properties with the ordinary carbon steel substrate.

[0027] The plain carbon steel with the ultra-thin iron-based coating described in the present invention has excellent wear resistance and corrosion resistance, so that the material has a longer service life.

[0028] In some embodiments, the hardness of the iron-based coating is 670-1220 HV, and the corrosion current density is 0.9 μA / cm 2 the following. DETAILED DESCRIPTION

[0029] The plain carbon steel with an ultra-thin iron-based coating and the method for manufacturing the same described in the present invention will be further explained and illustrated below in conjunction with specific embodiments. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.

[0030] Embodiments 1-5 of the present invention are all prepared by the following steps:

[0031] (1) Pretreatment and preparation of plain carbon steel substrate.

[0032] Exemplarily, in some embodiments, preprocessing may include the following steps:

[0033] Q345B, 45#, and T9 steel piston tubes with a thickness of 10 mm and an outer diameter of 200 mm were selected as specimens of plain carbon steel substrates, respectively.

[0034] The samples were polished to remove oxidation, and all steel samples were polished to a smooth and bright surface. The purpose of polishing is to eliminate the microscopic unevenness of the sample surface and give it a mirror-like appearance.

[0035] Then ultrasonic cleaning is performed: the sample is placed in a beaker filled with anhydrous ethanol, and then the beaker is placed in an ultrasonic cleaning machine for ultrasonic treatment. The main purpose is to remove organic matter, oil stains, and fine adhesion on the electrode surface.

[0036] The cylindrical specimen is then mounted on a fixture fixed to the HDED machining center. The HDED system has a continuous wave fiber laser (LDF-6000, IPG) with a maximum energy output of 6 kW, a laser head, a five-axis machining center with an allowable rotation speed of 800-1200 rpm, and a double-barrel powder feeder (RC-PGF-D2).

[0037] (2) A high-speed direct energy deposition process is used to deposit iron-based alloy powder on the surface of a plain carbon steel substrate to form an iron-based coating.

[0038] Among them, the parameters of the high-speed direct energy deposition process are as follows: the deposition speed is 20-60m / min, the power stability of the fiber laser is 1-3%, the central wavelength is 900-1080nm, and the feeding speed of the powder feeder is 60-150g / min.

[0039] The diameter of the iron-based alloy powder used is in the range of 25-53 μm.

[0040] In some more specific embodiments, the iron-based alloy powder is a low-carbon chromium-rich iron-based alloy powder, for example, the iron-based alloy powder contains 0.2-0.6% Cr and 0.2-0.4% C. In a specific example, the iron-based alloy powder contains 0.4% Cr and 0.3% C.

[0041] In Examples 1-5 of the present invention, X431 iron-based alloy powder is selected, and the iron-based alloy powder is nearly spherical.

[0042] In some more specific embodiments, the power adjustable range of the fiber laser can be 10-100%. The accuracy of the powder feeder can be 1-2g / min. The laser head is an annular coaxial powder feeding deposition head, which is internally water-cooled.

[0043] Table 1 lists the specific parameters of the high-speed direct energy deposition process in Examples 1-5 of the present invention.

[0044] (3) The iron-based coating is subjected to hot isostatic pressing to obtain plain carbon steel having the iron-based coating.

[0045] In some embodiments, the parameters of the hot isostatic pressing process are as follows: laser power is 2200-3000 W, overlap rate is 50-70%, powder feeding rate is 10-15 g / min, laser spot diameter is 0.8-1.2 mm, and defocusing amount is 5-10 mm.

[0046] Table 2 lists the specific parameters of the hot isostatic pressing step in Examples 1-5 of the present invention.

[0047] Table 1 lists the specific process parameters of the high-speed direct energy deposition process used in Examples 1-5 of the present invention.

[0048] Table 1.

[0049]

[0050] Table 2 lists the specific process parameters of the hot isostatic pressing treatment used in Examples 1-5 of the present invention.

[0051] Table 2.

[0052]

[0053] In order to verify the technical effects of the plain carbon steel with ultra-thin iron-based coating prepared in each embodiment of the present invention, the microhardness, wear and corrosion resistance of the plain carbon steel were tested, and the results are listed in Table 3. Among them:

[0054] Microhardness Test: The microhardness of the thermal spray coating was measured by a TIME GROUP INC-1000 automatic digital display Vickers hardness tester at intervals of 8-10 microns and for 10-15 seconds under a load of 1 N. The average value was determined from three measurement data based on the indentation at each depth interval.

[0055] Wear test: The wear behavior of the coating was tested using an HT-1000 wear tester with a load of 300-500 g, a wear radius of 0.5-2 mm, a motor frequency of 6-10 Hz, a speed of 380-560 r / min, and a loading time of 20-30 min. Before the wear test, the coating surface was mechanically ground and polished. The corresponding wear morphology was presented by LSCM and SEM equipped with an energy dispersive spectrometer (EDS).

[0056] Corrosion test: A classic three-electrode configuration (Solartron 1260A / 1287A) including a saturated calomel electrode (SCE), a Pt electrode, and a working electrode was immersed in a 3.5wt% NaCl solution for corrosion resistance measurement. Electrochemical measurements included potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) to evaluate corrosion behavior. Before electrochemical measurements, all samples were immersed in the solution until the open circuit corrosion potential reached equilibrium. In the potentiodynamic polarization test, the scan rate was fixed at 1.7-2mV / s and the voltage range was ±300mV. In the EIS test, the stable frequency range (10-2-105Hz) and the voltage amplitude were ±5mV.

[0057] In addition, the microstructure of the iron-based coating was observed using a scanning electron microscope, and the observation results are also listed in Table 3.

[0058] Table 3.

[0059]

[0060] It can be seen from the test results in Table 3 that, from the perspective of microstructure, the iron-based coating of the plain carbon steel in each embodiment of the present invention presents a stacked lamellar structure with a dense structure, and there are no holes or cracks even when observed at 800 times magnification.

[0061] In addition, the iron-based coating has a higher hardness, reaching 670-1215HV.

[0062] In addition, the wear loss of each example is 58-86 mg, indicating that it has excellent wear resistance.

[0063] In addition, the corrosion current density of each embodiment is 0.11-0.88 μA / cm 2 The size of the corrosion current reflects the strength of the corrosion resistance. The smaller the current density, the better the corrosion resistance. This shows that the coating of the present invention has excellent corrosion resistance.

[0064] In addition, the charge transfer resistance of each embodiment of the present invention is 2332-4623Ω, which represents the difference in corrosion resistance of different coatings. The larger the charge transfer resistance, the better the corrosion resistance of the material. Because the essence of metal corrosion is charge transfer ion exchange, when the resistance is large, the charge transfer speed will slow down, that is, the corrosion rate will decrease, which means that the material has better corrosion resistance; conversely, the resistance is small, which means that the material has poor corrosion resistance. It can be seen that the charge transfer resistance in each embodiment of the present invention is relatively large, which also shows that the present invention has good corrosion resistance.

[0065] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.

[0066] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.

Claims

1. A plain carbon steel with an ultra-thin iron-based coating, comprising a plain carbon steel substrate, characterized in that: The surface of the plain carbon steel substrate is provided with an iron-based coating, and the iron-based coating is a lamellar structure formed by stacking iron-based alloy powders.

2. The plain carbon steel with an ultra-thin iron-based coating as claimed in claim 1, characterized in that: The iron-based alloy powder contains Cr and C elements.

3. The plain carbon steel with ultra-thin iron-based coating according to claim 1, characterized in that: The iron-based coating is stacked by adopting a high-speed direct energy deposition process.

4. The plain carbon steel with an ultra-thin iron-based coating as claimed in claim 1, characterized in that: The single-side thickness of the iron-based coating is 60-150 microns.

5. The plain carbon steel with ultra-thin iron-based coating as claimed in claim 1, characterized in that: The hardness of the iron-based coating is 670-1220 HV, and its corrosion current density is 0.9 μA / cm 2 the following.

6. A method for producing plain carbon steel with an ultra-thin iron-based coating as claimed in any one of claims 1 to 5, characterized in that: Includes steps: A high-speed direct energy deposition process is used to deposit iron-based alloy powder on the surface of a plain carbon steel substrate to form an iron-based coating, wherein the deposition speed is controlled to be 20-60 m / min; The iron-based coating is subjected to hot isostatic pressing.

7. The manufacturing method according to claim 6, characterized in that: The parameters of the high-speed direct energy deposition process meet the following requirements: the power stability of the fiber laser is 1-3%, and the central wavelength is 900-1080 nm.

8. The manufacturing method according to claim 6, characterized in that: The parameters of the high-speed direct energy deposition process are as follows: the feeding speed of the powder feeder is 60-150 g / min.

9. The manufacturing method according to claim 6, characterized in that: The parameters of the hot isostatic pressing process meet at least one of the following items: laser power is 2200-3000W, overlap rate is 50-70%, powder feeding rate is 10-15g / min, laser spot diameter is 0.8-1.2mm, and defocus amount is 5-10mm.

10. The manufacturing method according to claim 6, characterized in that: The diameter of the iron-based alloy powder is in the range of 25-53 μm.

Citation Information

Patent Citations

  • Iron-based alloy powder for manufacturing diesel engine piston ring groove applied to low-speed and heavy-load ships through laser

    CN106480380A

  • High-hardness iron-based powder for ultra-high-speed laser cladding and preparation method thereof

    CN110878413A

  • Corrosion-resistant and wear-resistant iron-based laser cladding alloy powder and laser cladding method thereof

    CN111218682A

  • Hot isostatic pressing method for laser additive manufacturing of 24CrNiMo alloy steel

    CN113649594A

  • Iron based alloy suitable for providing a hard and wear resistant coating on a substrate, article having a hard and wear resistant coating, and method for its manufacture

    US20210147967A1